Virtual chemithon and physicsthon - Abdul Wahab, Nor Aimi; Hasan, Suhaiza; Mohd Fuad, Nur Adriana Nisa; Abdul Hamed, Alya Nurazmina; Awang Damit, Dayang Nur Fatin Nadhirah (2022)
The pandemic COVID-19 has become a global health issue and has had a major impact on education. The way of learning has changed from face to face classes to online distance learning (ODL), whereby learning is undertaken remotely on the digital platform. Research has shown that online learning has the advantage of high efficiency, accessibility of time and place, and suits various learning styles. Despite these advantages, the student still finds it difficult to undergo online learning due to lack of focus, technology issues and longer screen time. As a result, most students feel demotivated, burnt out, and bored with the same routine during online classes. A survey conducted at UiTM Cawangan Pulau Pinang among pre-science students on the perceptions towards the final exam for chemistry and physics subjects shows that 70% of the students feel stressed about the exam, and 59% is not confident enough to score A for both subjects. One of the reasons is that students find chemistry and physics subjects difficult to understand and what's more with online learning. Using old and conventional revision styles with long ODL sessions worsens student performance. Thus, to help students better prepare for the chemistry and physics examination, a new semi-guided revision learning style that combines physical activity and practice questions has been developed. "Virtual Chemithon and Physicsthon '' was created to help students understand and systematically revise the course, which could lead to better performance in both subjects. This Virtual Chemithon and Physicthon not only help the student to revise and answer the question for the preparation of the final exam but also encourages the student to lead a healthy lifestyle and enhance the student's happiness index. The Virtual Chemithon and Physicshton come with an e-template and where students need to complete the task and submit the e-template online to get an e-certificate. Students are required to answer all questions from each chapter and complete a 1-3 km run between chapters. At the end of this semi-guided revision, the student answered all questions and simultaneously completed a 10 km run. This new revision style ensures students have breaks between studies and encourages them to exercise. It also helps increase brain speed, improve emotional health, wellbeing and reduce stress. Research has also revealed that exercise after revision can help students retain information. It is hoped that using this semi-guided new revision style could improve students' performance in physics and chemistry.